(untitled) - Churchill, Gilbert A (Orlando, Florida, 1999)
This is a textbook for the introductory sequence in marketing research at either the undergraduate or the graduate level. Among the changes in this edition (fifth was 1991) are an increased emphasis on the international aspects of marketing, on marketing research in service settings, and on marketing to organizational buyers. More than 25% of the cases are new and another 30% have been revised
Keywords: Marketing research